2021
DOI: 10.1002/admi.202001922
|View full text |Cite
|
Sign up to set email alerts
|

3D Ordered Co@NC Skeleton for Bifunctional Oxygen Reduction and Oxygen Evolution Reaction Electrocatalysts

Abstract: SiO 2 opals templates. [35,36] Nevertheless, the thickness of self-assembled opals templates is generally below 5 µm, far from providing sufficient interface area for ORR and OER. [37,38] Herein, we developed a novel thickfilm air electrode for ZABs, consisting of 3DOM carbon structure and sufficient exposed CoN x and Co nanoparticles active sites. This novel air electrode bases on thick SiO 2 opals template, in which carbon fiber paper was utilized as a support for releasing the stress during SiO 2 spheres se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Cai et al reported a 3D porous Co@N-C catalyst composed of abundant CoN x and Co nanoparticles embedded in carbon networks, which facilitated the ORR and OER kinetics. [298] Besides, the zinc-air batteries assembled with the catalyst exhibited a high power density (150 mW cm −2 ), a high specific energy density (964.2 W h kg −1 ), and sufficient cycling stability (730 cycles with 10 mA cm −2 charge/discharge current density). N-doped hollow porous carbon nanofibers with incorporated Co nanoparticles were also reported by Lu et al using electrospinning and ultrafast high-temperature shock technique (Figure 17a,b).…”
Section: Metal-nitrogen-doped Carbon (M-n-c)-based Electrocatalystsmentioning
confidence: 99%
“…Cai et al reported a 3D porous Co@N-C catalyst composed of abundant CoN x and Co nanoparticles embedded in carbon networks, which facilitated the ORR and OER kinetics. [298] Besides, the zinc-air batteries assembled with the catalyst exhibited a high power density (150 mW cm −2 ), a high specific energy density (964.2 W h kg −1 ), and sufficient cycling stability (730 cycles with 10 mA cm −2 charge/discharge current density). N-doped hollow porous carbon nanofibers with incorporated Co nanoparticles were also reported by Lu et al using electrospinning and ultrafast high-temperature shock technique (Figure 17a,b).…”
Section: Metal-nitrogen-doped Carbon (M-n-c)-based Electrocatalystsmentioning
confidence: 99%
“…The Fe 3 C-FeSA@3DCN supported by foamed nickel was used as the air cathode, zinc foil was used as the anode, and a gel electrolyte was used as the conductive layer, and the solid-state flexible battery was assembled (Figure a) Figure b shows that the open-circuit voltage of the prepared gel solid-state battery is 1.372 V, and the open-circuit voltage is very stable.…”
Section: Resultsmentioning
confidence: 99%
“…In the process of calcination, NaCl, as an activator, can introduce more pore structures and carbon defects, expose more active sites, and adjust the surface properties of carbon atoms in the material. However, these are not sufficient to meet the requirements for ORR activity. The introduction of N atoms larger than C into MOFs may cause a higher strain at their edges, thus promoting the charge potential and chemical adsorption of oxygen, which are the main reasons for the enhanced ORR activity. Many reports have confirmed that N doping, mostly in the form of pyridine nitrogen and graphite nitrogen, can effectively improve the ORR activity of catalysts. , It is widely acknowledged that urea is the most popular nitrogen source due to its low cost and high content of nitrogen. More importantly, urea is more likely to synthesize the catalytic sites such as pyridine nitrogen and graphite nitrogen during the process of high-temperature pyrolysis. , …”
Section: Introductionmentioning
confidence: 99%